Evaluation and Comparison of some Infiltration Models on Agricultural Soils of Bosso Local Government Area, Niger State, Nigeria - Musa, J. J.; Kuti, I. A.; Dada, P. O. O.; Otuaro, E. A.; Eze, P. C.; Nathaniel, S. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Over the last few decades, researchers have developed a great interest in fabricating and synthesising zinc silicate-based glass ceramics. However, using waste materials as precursors for the fabrication is yet another milestone in waste management. Thus, this study fabricated zinc silicate glass-ceramic using sola lime silica (SLS) glass waste as a silicon source. The series of precursor glass in the  the conventional solid-state melt-quench technique prepared system through a controlled crystallisation process. The glass system’s physical, structural, and optical properties were obtained by density measurement, X-Ray diffraction, Fourier Transform Infrared Spectroscopy, and Ultraviolet-visible spectroscopy, respectively. The density of the   glasses series was observed to be decreasing with the increment of  content. The XRD spectra of the   samples with 0 and 0.01 wt.% , exhibits major diffraction peaks attributed to the ZnO phase in the glass matrix. However, as  content  increased, the precursor glass sample shown by the XRD spectra depicted a broad halo characteristic, which reflected the properties of amorphous glass that were observed at the composition of 0.05 wt.%  From FTIR spectra, the bands at 500, 688, 902 and 1243  can be associated with stretching vibrations of ZnO4 and Si-O-B bending vibrations, stretching vibrations of the B–O bonds in the  units, and modes of boron–oxygen triangular units. The intensity of the IR band increases with increasing percentage of . The UV-Vis analysis of the samples with 0 and 0.01 wt.%  demonstrates crystalline hump and varies at 370 nm. It was observed that the addition of B2O3 to the ZnO-SLS glass network caused the glassy amorphous state without a sharp absorption edge at 0.05, 0.10, and 0.15 wt.% B2O3.The  system  shows the increase in band gap when the composition of   increased. When  serves as a modifier, the number of NBOs will increase, and this will cause the expansion of glass network. The zinc silicate-based glass-ceramic produced has been classified as a semiconductor due to the vast optical band gap energy obtained and may have vital potential applications for future LED and other optoelectronic lighting devices.